Introducing the 21st Century Boulevard: A Post-Covid Response to Urban Regeneration of Main Road Corridors, - Newman, Peter; Hargroves, Karlson; Desha, Cheryl; Idzapani, Parisa (Scientific Research Publishing, 2021)
As city leaders contemplate the post-COVID-19 urban regeneration, Parisian Boulevards from the 17th Century provide inspiration, from their combination of mobility with pedestrian, nature and place-based qualities. This paper proposes a new concept called “21st Century Boulevards” to support local and regional authorities in achieving urban regeneration using such qualities together with new technology. Four approaches are recommended to create 21st Century Boulevards: 1) enhancing road-based shared transit systems such as electric trackless trams; 2) embedding micro-mobility and autonomous shuttles for end-of-trip integration at stations; 3) adopting new precinct-scale technologies that enable Net Zero outcomes for station precincts such as renewable energy recharge hubs, and 4) implementing a smart cities-based demand management system. The human qualities of boulevards are outlined using new planning and design approaches. A key indicator of success would be to measure the extent of a new parameter called the “Busker Factor”. The integration of new technology and new planning to achieve centuries-old urban qualities is a regeneration opportunity with multiple benefits for the main roads of all cities.